The representation of ordinary people: A discursive study of identities constructed in China's news reports of social conflicts. (December 2018) - Ge, Yunfeng; Wang, Hong
Highlights: Ordinary people are represented either positively or negatively. Antagonistic, jural, and harmonious relations are constructed. Super-ordinate identities are constructed for ordinary people. Intertextuality and interdiscursivity are frequently used discourse strategies. Abstract: The development of information technologies has made traditional news media aware of a public desire for bottom-up participation in the news production process. As a result, ordinary people have frequently participated in or even become the focus of news output. By following van Dijk's socio-cognitive approach of critical discourse analysis, this article examines how ordinary people are represented in China's news reports of social conflicts. The data include 106 news reports collected from the state-run websites of Xinhuanet and People's Network. Analytical results show that ordinary people have an either positive or negative representation in three relations constructed between ordinary people and government institutions, namely, antagonistic, jural and harmonious relations. It has also been found that journalists construct super-ordinate identities for ordinary people and represent them either positively as advocates of government policies or negatively as violators of social rules. The representation of both identities and relations of ordinary people is realized through both macro and micro discourse strategies. In essence, the complex representation of identities and relations is the result of the diversified ideologies underlying China's news reports.